The Impacts of Increased Labor Productivity of the Service Sector in Thailand: Analysis of Standard Computable General Equilibrium (CGE) Model - Luksamee-Arunothai, Mana; Toprayoon, Yannakorn; Jaroenjitt, Roongrattana (International Journal of Multidisciplinary in Management and Tourism, 2020)
This paper aims to investigate the impact magnitude of the increased labor productivity in the service sector both at macro and sectoral levels. Due to Thailand’s service sector having shown the lower productivity growth than other sectors, this reflects a lack of knowledge and skills as well as industry-related work environment problems. This study is unlike the majority of previous empirical research studies which mainly intended to calculate labor productivity or to study factors affecting labor productivity or the causes of low labor productivity in Thailand. This study employs a standard computable general equilibrium (CGE) model to analyze the impact magnitude. The database was compiled using the 2010 social accounting matrix (SAM) which has 21 sectors to analyze. Three different scenarios were simulated for the service sector in Thailand with the labor productivity increased by 1, 2 and 3% relative to the baseline scenario. The results reveal the real Gross Domestic Product (GDP) increases by 1.75, 2.19 and 2.64% and the total domestic output increases by 1.16, 1.45 and 1.75%, respectively. The direct effect on domestic output when the labor productivity increased mostly occurs in Public Administration sector, followed by Education sector, Hospital sector, Finance, Banking and Insurance sector, Wholesale-Retail Trade and Other Services sector, Communication sector, Transportation and Logistics sector, Electricity and Water Supply System sector, Real Estate sector and Construction sector, respectively. While the indirect effect on domestic output when the labor productivity increased mostly happens in Paper Industries and Printing sector, Mining and Quarrying sector, Rubber, Chemical and Petroleum Industries sector, Metal, Metal Products and Machinery sector and Food Manufacturing sector, respectively. The reason being that these sectors are more upstream and are highly inter-linked with other service sectors in Thailand.